Colour and Other Related Quality Characteristics of Canned Pineapple (Ananas Comosus L. Merr.) as Affected by Storage Period and Canning Media - Kanniah, Jayashree (2002)
The effects of storage period and canning media on canned pineapple (Ananas comosus L. Merr.) slices (CPS) were determined. The canned pineapples were stored at ambient temperature for 6 and 12 months with 0 month acting as the control. The pineapple slices were canned in media containing pineapple juice and light and heavy syrup. The CPS studied belonged to grades Standard, Choice and Fancy according to the Malaysian Standard Specifications for Canned Pineapples (MSSCP). The experimental design was a randomized complete block design with a factorial arrangement of treatments (3 storage period x 3 types of canning media), and with three replications. The results indicated that the can vacuum and can headspace were not affected by storage period and cann ing media. Values of lightness and hue decreased gradually in CPS canned in pineapple juice and heavy syrup when stored after 6 months. CPS in light syrup had the lowest hO compared to those in pineapple juice and heavy syrup. Flesh firmness of Standard and Choice grades CPS showed sharp decreased after 6 and J2 months storage. Fancy grade showed a gradual decrease in flesh firmness throughout the storage period. Standard and Choice grades CPS canned in pineapple juice and heavy syrup had firmer flesh throughout the storage period compared to those in light syrup. Standard and Choice grades CPS showed sharp increases in soluble solids concentration (SSC) after 6 and 12 months storage. CPS in pineapple juice and heavy syrup showed gradual increased in SSC throughout the storage period. The percentage of B-carotene was highest in Standard grade CPS in heavy syrup, followed by pineapple juice and light syrup. Choice grade CPS canned in pineapple juice and heavy syrup showed higher percentages of B-carotene compared to those in light syrup, whereas Fancy grade CPS in light syrup showed the lowest percentage of B-carotene. B-carotene was positively and significantly correlated with L * and hO colour values indicating that CPS with high amount of B-carotene were lighter yellow. The results of this research can be used to develop the quality criteria of canned pineapples in the MSSCP so that the Malaysian canned pineapple can be more acceptable in the export markets.